Elongator Is Required for Root Stem Cell Maintenance by Regulating SHORTROOT Transcription. Issue 1 (6th November 2018) - Qi, Linlin; Zhang, Xiaoyue; Zhai, Huawei; Liu, Jian; Wu, Fangming; Li, Chuanyou; Chen, Qian
Abstract : Elongator subunits associate with the pre-mRNA of SHORTROOT and recruit RNAPII to the SHR gene body, and thereby contribute to root stem cell maintenance and radial patterning. Abstract: SHORTROOT ( SHR ) is essential for stem cell maintenance and radial patterning in Arabidopsis ( Arabidopsis thaliana ) roots, but how its expression is regulated is unknown. Here, we report that the Elongator complex, which consists of six subunits (ELP1 to ELP6), regulates the transcription of SHR . Depletion of Elongator drastically reduced SHR expression and led to defective root stem cell maintenance and radial patterning. The importance of the nuclear localization of Elongator for its functioning, together with the insensitivity of the elp1 mutant to the transcription elongation inhibitor 6-azauracil, and the direct interaction of the ELP4 subunit with the carboxyl-terminal domain of RNA polymerase II, support the notion that Elongator plays important roles in transcription elongation. Indeed, we found that ELP3 associates with the premessenger RNA of SHR and that mutation of Elongator reduces the enrichment of RNA polymerase II on the SHR gene body. Moreover, Elongator interacted in vivo with SUPPRESSOR OF Ty4, a well-established transcription elongation factor that is recruited to the SHR locus. Together, these results demonstrate that Elongator acts in concert with SUPPRESSOR OF Ty4 to regulate the transcription of SHR .